Autoantibodies to recombinant lipocortin-1 in rheumatoid arthritis and systemic lupus erythematosus. Issue 10 (October 1989) - Goulding, N J; Podgorski, M R; Hall, N D; Flower, R J; Browning, J L; Pepinsky, R B; Maddison, P J
Abstract : Corticosteroids may mediate some of their anti-inflammatory effects via induction of a specific 38 kD protein, lipocortin-1. Autoantibodies to lipocortin-1 were measured by enzyme linked immunosorbent assay (ELISA) in 90 healthy subjects and in 63 patients with rheumatoid arthritis (RA), 36 with systemic lupus erythematosus (SLE), 26 with polymyalgia rheumatica, and 13 with chronic airways disease. Sixteen patients with RA receiving prolonged, high steroid doses (prednisolone greater than 7.5 mg/day) had raised IgM antilipocortin-1 levels, while 19 patients with RA untreated with steroids had normal levels. This association was independent of disease activity. In SLE, raised antilipocortin-1 levels were associated with active disease and were independent of steroid treatment. Antilipocortin-1 antibody levels were not raised in patients with polymyalgia rheumatica and chronic airways disease. Thus steroid treatment alone appears insufficient to induce antilipocortin-1 antibodies, unless an underlying autoimmune state is also present. In RA, antilipocortin-1 antibodies may impair anti-inflammatory actions of steroids and render some patients 'steroid resistant'.